The Syllable And Language Perception - Nathan, Geoffrey S. (Canadian Acoustics, 2022)
This paper proposes that languages have an active process of syllabification that takes a string of phonemes as input and organizes those sounds into a hierarchical syllable structure. This process acts as a filter on perception of input, such that native speakers hear both their own and foreign languages as if the sounds had been organized to follow the syllabification processes of this own language. The results of several psycholinguistic research programs can be offered as evidence for this claim.